Performance of an automated chemiluminescent immunoassay for SARS-COV-2 IgM and head-to-head comparison of Abbott and Roche COVID-19 antibody assays - CS, L. (Elsevier B.V., 2022)
10.1016/j.plabm.2021.e00230